μ-Raman spectroscopy characterization of LiNbO3 femtosecond laser written waveguides - Tejerina, M. R. (2012)
In this paper, we present an iterative method which merges experimental μ-Raman measurements and numerical simulations to describe femtosecond written waveguides in LiNbO3 crystals. This method is based on the deformation potential theory, and uses the finite element method to analyze elastic deformations after femtosecond laser micro-explosions in x-cut Mg:LiNbO3 crystals. The resultant strain and refractive index field after laser interaction were estimated and yielded similar values to those obtained in other works. The LiNbO3 Raman deformation potential constants were also estimated in this work.